PENAMPILAN KELINCI YANG DIBERI PAKAN DASAR RUMPUT DENGAN SUPLEMTASI KONSENTRAT DAN LEMAK TELO - SUMADI, I.K.; BUDAARSA, K. (Buletin Udayana Mengabdi, 2012)
ABSTRACT The experiment that aimed for knowing the influence of increase tallow into concentrate diet for rabbits performance that are given basic diet field grass had done. This experiment used Randomized Completely Design (RCD) with five treatments and each treatment consisted of four replicates. Those five treatments were concentrate diet without tallow (treatment A) and concentrate diet with 2%, 4%, 6% and 8% tallow (followed as treatment B, C, D and E). The research had done into diet consumption, energy consumption, protein consumption, crude fiber consumption, calcium consumption, phosphor consumption, body weight gain, final body weight and FCR. The result of this experiment showed that diet consumption, crude fiber consumption, calcium consumption, phosphor consumption, body weight gain and final body weight for all treatments were non significant different (P>0.05). Energy consumption and FCR were significant different (P<0.05). From the result can be concluded that the rabbits that have concentrate diet treatment with 6% tallow resulted the highest body weight gain and the lowest FCR.